Design of a 100-MeV compact VHEE beam line in Tsinghua University - Li, Hongyu; Zha, Hao; Lin, Xiancai; Gao, Qiang; Liu, Focheng; Shi, Jiaru; Chen, Huaibi (Frontiers in Physics, 2025)
A 100-MeV Compact Electron Accelerator design has been proposed for Very High Energy Electron (VHEE) radiotherapy research at Tsinghua University. The microwave source for this system is a 50 MW X-band klystron, paired with a pulse compressor featuring a correction cavity chain. During high-power test, the system achieved a flat-top power gain three times the input. The acceleration system consists of three main components: a backward traveling-wave buncher that bunches and accelerates electrons from a thermionic cathode gun to 8 MeV, followed by two 72-cell X-band constant-gradient traveling-wave accelerating structures, which further increase the electron energy to 100 MeV with a gradient of 80 MV/m. The total length of the system is 1.8 m, and its design is detailed in this paper.